2021
DOI: 10.1136/ijgc-2020-001750
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic and obstetric outcomes after simple conization for fertility-sparing surgery in FIGO 2018 stage IB1 cervical cancer

Abstract: ObjectiveConization/simple trachelectomy is feasible in patients with early-stage cervical cancer. Retrospective data suggest that conization with negative lymph nodes could be a safe option for these patients. This study aims to provide oncologic and obstetric outcomes of a large series of patients with 2018 International Federation of Gynecology and Obstetrics (FIGO) stage IB1 cervical cancer managed by conization.MethodsPatients with early cervical cancer and a desire to preserve fertility who underwent con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…2 In our study, the odds of preterm birth before 37 weeks of gestation were approximately double among patients with cervical cancer compared with those in the control groups, consistent with prior studies. 6,10,[32][33][34] Our study design allows for more reliable estimates compared with case series with few pregnancies and limited obstetric outcomes, [11][12][13][14][15][16][17][18] systematic reviews that pool these same uncontrolled studies, 7,9,10 and population-based studies that used International Classification of Diseases codes to identify cancer diagnoses. 20 Our findings are consistent with those of a database study by Hartnett and colleagues 8 that demonstrated a 28% rate of preterm birth before 37 weeks of gestation, which translated to more than double the risk of preterm birth compared with the control groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 In our study, the odds of preterm birth before 37 weeks of gestation were approximately double among patients with cervical cancer compared with those in the control groups, consistent with prior studies. 6,10,[32][33][34] Our study design allows for more reliable estimates compared with case series with few pregnancies and limited obstetric outcomes, [11][12][13][14][15][16][17][18] systematic reviews that pool these same uncontrolled studies, 7,9,10 and population-based studies that used International Classification of Diseases codes to identify cancer diagnoses. 20 Our findings are consistent with those of a database study by Hartnett and colleagues 8 that demonstrated a 28% rate of preterm birth before 37 weeks of gestation, which translated to more than double the risk of preterm birth compared with the control groups.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Observational studies have demonstrated that more than a third of cervical cancer survivors who ultimately conceive will deliver prematurely. [7][8][9][10] However, the available data are limited because they are derived from case series [11][12][13][14][15][16][17][18] and systematic reviews of case series with few pregnancies. 7,9,10 Population-based studies have included more pregnancies after cervical cancer surgery but often lack a rigorous definition of pregnancy timing related to cancer diagnosis, 8,19 match control group participants to case group participants on few demographic variables, 8,19 or summarize outcomes from patients with different types of reproductive cancers.…”
mentioning
confidence: 99%
“…Multiple studies investigated the results of fertility-sparing treatment in the early stages of cervical cancer and considered the subsequent pregnancies and their outcomes [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ]. Anderson et al (2018) studied the pregnancy rate in women with a history of previous cancer and compared it to that of women from the general population ( Table 1 ) [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…26 Complication rates and risk of postoperative cervical stenosis (7%) are lower than with VRT and ART, and recurrence rates are concordant with prior retrospective data (3.5%). [27][28][29][30]…”
Section: Conizationmentioning
confidence: 99%